Negative attitudes toward older adults: Subjective time to become older and "stereotype embodiment theory"-based intervention. (19th September 2022) - Grassi, Massimo; Shimizu, Yuho
Abstract: Reducing negative attitudes toward older adults is an urgent issue. A previous study has conducted "stereotype embodiment theory"-based interventions (SET interventions) that present participants with the contents of SET and related empirical findings. I focus on the subjective time to become older (the perception of how long people feel it will be before they become old) as a mechanism for the effect of SET interventions. I make the SET intervention group and the control group in which the participants are presented with an irrelevant vignette. The data from 641 participants ( M = 31.97 years) were analyzed. Consequently, the SET intervention shortened the subjective time to become older and reduced negative attitudes toward older adults. When considering SET interventions, it would be useful to focus not only on the self-interested motives to avoid age discrimination but also on the subjective time to become older.